INVESTIGATING THE LEVEL OF AWARENESS REGARDING INFORMED CONSENT AMONG THE POST-OPERATIVE PATIENTS IN SURGICAL WARD (Journal of Medical & Health Sciences Review, 2025)
Background: The concept of informed consent is an important aspect of biomedical ethics, which is obtained in written form, but in some cases, it may be verbal, especially for non-invasive and relatively non-risky interventions. The study was conducted with the aim of evaluating the level of awareness among post-operative patients regarding informed consent.Methodology: The study design was cross-sectional descriptive and was conducted in the surgical ward of a tertiary care hospital in Swat, Pakistan from December 2023 to January 2024. The sample size of the study was 180 using the purposive sampling technique, while a valid and reliable questionnaire was used for data collection. Descriptive statistics were used through SPSS 22.0. The study was approved by an ethical review committee, and informed consent was obtained from every respondent.Results: The finding reveals that the majority of the participants were female 112 (55.7%), the age group 36–45 years was 75 (37.3%), and people belonged to village 189 (94%). The maximum number of patients level of awareness was good (58%), while the remaining 42% had a poor level of awareness. The majority of the patients know the type of surgery 181 (90%), alternative treatment to the surgery 123 (61.2%), number of hours to be nothing per oral (NPO) 190 (94.5%), time of surgery 197 (98%), and overall satisfaction regarding informed consent 201 (100%).Conclusion: The study found that patients lack awareness about the surgeon, procedure process, advantages and disadvantages, procedure importance, anesthesia type, and complications, highlighting the need for enough information regarding their procedure.